Use of Biologic Agents in Extremity Reconstruction - Grush, Andrew E.; Depani, Monal; Parham, Matthew J.; Mejia-Martinez, Valeria; Thornton, Alexandra; Sammer, Douglas M. (Seminars in Plastic Surgery, 2022)
Skin and soft tissue defects of the lower extremity present a unique challenge for the reconstructive surgeon. Successful repair of the lower extremity relies not only on strong anatomical knowledge and surgical expertise, but also on careful consideration of the numerous preoperative factors and indications that may alter the patient's response to operative management. While many of these injuries result from burns, avulsive trauma, diabetes, or vascular insufficiencies, a significant portion can be associated with resection of neoplastic pathologies. This review outlines the uses, indications, and considerations for biologic wound agents in reconstructing skin and soft tissue defects of the lower extremity following Mohs micrographic surgery.
Keywords: Mohs micrographic surgery; lower extremity; Integra; fasciocutaneous flap; melanoma; cutaneous malignancies